Peran Guru Aqidah Akhlaq Dalam Menanamkan Nilai-Nilai Moralitas Siswa SMP Aisyiyah Curup - Siti Bandiah (SALIHA: Jurnal Pendidikan & Agama Islam, 2020)
This study aims to answer the researcher's questions, yes. what is the moral condition of the students and what are the efforts of the morality teacher in instilling the values ​​of Student Morality in Aisyiyah Curup "Middle School". This research method is qualitative descriptive which is the subject of this study aqidah moral teacher, headmaster, teachers and 4 students representing classes VII, VIII, IX. From the results of the study illustrate the role of the aqidah moral teacher to instill the values ​​of morality of students. With coaching, habituation, direction, advice, adherence instilled in student behavior such as courtesy to teachers, obeying school rules and holding Islamic holidays and religious programs that will shape student morals so that students can behave commendably and can be reflected in behaviors that are well. From this study the authors hope to the principal, the teachers to be able to increase efforts to instill the moral values ​​of students and can apply good moral values ​​in daily life.